Belçika’daki Türkiye Kökenli Öğrencilerin ve_x000D_ Velilerin Türkiye’deki Öğrenci ve Velilerden_x000D_ Farklılıkları - DENİZ, LEVENT (My University, 2020)
Belçika’daki Türkiye kökenli öğrenciler, veliler ile Türkiye’deki öğrenciler, veliler arasındaki farklılıklarıbelirlemek amacıyla Türkçe ve Türk kültürü dersi (TTKD) öğretmenlerinin görüşleri alınmıştır. Buçalışmada nitel araştırmanın fenomenoloji deseni kullanılmıştır. Açık uçlu sorulardan oluşan yarı yapılandırılmış görüşmeler yoluyla elde edilen 10 katılımcıya ait veriler içerik analiziyle çözümlenmiş vekategorilere ayrılmıştır. TTKD öğretmenlerine göre, Belçika’daki Türkiye kökenli öğrenciler yaparakyaşayarak öğrenmekte ve okul dışı gezilere, etkinliklere daha çok katılmaktadırlar. TTKD’de uymasalarda okul ve sınıf kurallarına daha çok uymaktadırlar. Türkçe öğretimi, çoğu öğrenci için yabancı dil öğretimidir. Çiftdilli olmayan öğrencilerde Fransızcayı öğrenme güçlüğü çekenlerin sayısı fazladır. Öğrencilerin çoğu bir meslek sahibi olmak için asgari düzeyde eğitim görmekte veya işsizlik parası almakistemektedirler. Belçika’nın her yerinde olmasa bile öğrenciler farklılıklara karşı daha hoşgörülüdür. Belçika’daki Türkiye kökenli velilerin çoğu öğrencilere yeterli eğitsel ve sosyal desteği sağlayamamaktadır.Eğitim düzeyi yüksek veliler dışında genelde veliler TTKD’ye gereken önemi vermemekte ve dersin başarısı için öğretmenlerle işbirliği yapmamaktadır.

Opinions of Turkish and Turkish culture course (TTCC) teachers were received in order to determine_x000D_ the differences between Turkish origin students and parents in Belgium and students and parents in_x000D_ Turkey. In this study phenomenology pattern which is one of the qualitative research methods was used._x000D_ Data belonging to 10 participants, which was obtained by semi structured interviews consisting of open_x000D_ ended questions were resolved by content analysis and were separated into categories. According to_x000D_ TTCC teachers Turkish origin students in Belgium learn by hands on learning, participate in trips out_x000D_ of school and are involved in extracurricular activities much more than the students in Turkey. Although they do not comply during TTCC, they are more in compliance with school and classroom rules in_x000D_ Belgium. Teaching Turkish is the teaching of foreign language for most Turkish origin students. The_x000D_ number of non-bilingual students who have difficulty learning French is high. Most of the students have_x000D_ a minimum level of education in order to have a profession and they want to receive unemployment_x000D_ benefits. Students are more tolerant to race, ethnic, sex, cultural… differences, even if not all over Belgium. Most of Turkish origin parents in Belgium cannot provide students with adequate educational_x000D_ and social support. Apart from parents with high educational level, parents generally do not give due_x000D_ importance to TTCC and do not cooperate with teachers for the success of the course.
Differences of Turkish Origin Students and Parents in Belgium From Students and Parents in Turkey